Measurement Invariance of the ADHD Rating Scale–IV Home and School Versions Across Age, Gender, Clinical Status, and Informant. (January 2021) - Dobrean, Anca; Păsărelu, Costina-Ruxandra; Balazsi, Robert; Predescu, Elena
The present study aimed to investigate the measurement invariance across age, gender, clinical status, and informant of the Attention-Deficit/Hyperactivity Disorder Rating Scale–IV (ADHD-RS-IV) Home and School versions. The participants were 1, 106 Romanian children and adolescents (mean age = 12.74 years, standard deviation = 2.84, age range 6-18 years). Both parents and teachers assessed ADHD symptoms. The factorial structure of the scale was assessed using confirmatory factor analysis, and measurement invariance was assessed using multigroup confirmatory factor analysis. The results supported the reliability of the ADHD-RS-IV, with high internal consistency coefficients for both versions. Confirmatory factor analysis validated a two-factor model. Multigroup confirmatory factor analysis confirmed the measurement invariance of ADHD-RS-IV across age, gender, clinical status, and informant. ADHD-RS-IV had good psychometric properties in a sample of Romanian children and adolescents. It is a reliable instrument given its strong invariance. Implications for evidence-based assessment of ADHD are discussed.